Tanzania's Equilibrium Real Exchange Rate - Hobdari, Niko. (Washington, D.C. : International Monetary Fund, 2008)
Tanzania's real effective exchange rate (REER) has depreciated sharply since end-2000, reversing the appreciation that took place in the second half of the 1990s. Single-country and panel data estimates, and the external sustainability approach, suggest that Tanzania's REER is currently modestly undervalued relative to its estimated equilibrium level. Looking forward, a modest trend appreciation of the equilibrium REER is expected, consistent with continued high GDP growth and an expected recovery in terms of trade. In addition, capital inflows to Tanzania could be significantly higher than currently expected, to take advantage of Tanzania's natural resources and strong policy framework. If so, these inflows would contribute to an additional appreciation by as much as 20 percent of the equilibrium REER.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet